Variety of the drift pumice clasts from the 2021 Fukutoku‐Oka‐no‐Ba eruption, Japan. (9th February 2022) - Yoshida, Kenta; Tamura, Yoshihiko; Sato, Tomoki; Hanyu, Takeshi; Usui, Yoichi; Chang, Qing; Ono, Shigeaki
Abstract: Pumice rafts that arrived at the Nansei Islands, Japan, provided a unique opportunity to investigate the Fukutoku‐Oka‐no‐Ba (FOB) eruption of August 2021. Despite drifting for 2 months for 1300 km, the drift pumice raft had a large volume and contained a variety of pumice clasts, some of which were deposited during a high tide in a typhoon, while others were washed up on a sandy beach. Most of the drift pumice clasts are gray in color, vesicular, and have a groundmass containing black enclaves. Rare black pumice and the main gray pumice components have similar trachytic compositions, with SiO2 = 61–62 mass% and total alkalis = 8.6–10 mass% (on an anhydrous basis). Both pumice types contain clinopyroxene, plagioclase, and rare olivine phenocrysts. Thin‐section observations show that the gray pumice has more elongated vesicles as compared with the black pumice that has spherical vesicles, even where the two types of pumice are in the same clast. The glass in the black pumice is transparent and brown in color, while that in the gray pumice is colorless. No micro or nano‐crystals were observed during electron and optical microscopy. Raman spectra of the brown‐colored glass exhibit a clear magnetite peak, suggesting magnetite nanolites cause the brown color. High‐Mg olivine in the black pumice has an equilibrium temperature of c. 1200 °C and a rim diffusion profile indicative of re‐equilibration with the surrounding melt over a period of hours to days. The textural relationships between the gray and black pumice suggest that the black pumice had become black and viscous before the two types of pumice mixed. Therefore, crystallization of magnetite nanolites and a corresponding increase in melt viscosity were important in the eruption preparation process, which then resulted in a large‐scale Plinian eruption.